Psychological Stress and its Relationship with Achievement of Science Students of Kendriya Vidyalayas - Narendra Kumar,; Rajive Kumar, (JOURNAL OF INDIAN EDUCATION, 2013)
This study attempts to assess the psychological stress and its relationship with achievement among senior secondary science students of Kendriya Vidyalayas. They were administered Psychological Stress Scale for Science Students developed by the researcher, which measures 12 dimensions of psychological stress. Results show that the stress dimension associated with examination and achievement is the major factor causing stress, while health factors cause the least stress. Achievement of science students was significantly and negatively related with the content of science while positive significant relationship was observed with dimension of society.